Primordial Germ Cell Specification in Vertebrate Embryos: Phylogenetic Distribution and Conserved Molecular Features of Preformation and Induction - Hansen, Christina L.; Pelegri, Francisco (Frontiers in Cell and Developmental Biology, 2021)
The differentiation of primordial germ cells (PGCs) occurs during early embryonic development and is critical for the survival and fitness of sexually reproducing species. Here, we review the two main mechanisms of PGC specification, induction, and preformation, in the context of four model vertebrate species: mouse, axolotl, Xenopus frogs, and zebrafish. We additionally discuss some notable molecular characteristics shared across PGC specification pathways, including the shared expression of products from three conserved germline gene families, DAZ (Deleted in Azoospermia) genes, nanos-related genes, and DEAD-box RNA helicases. Then, we summarize the current state of knowledge of the distribution of germ cell determination systems across kingdom Animalia, with particular attention to vertebrate species, but include several categories of invertebrates – ranging from the “proto-vertebrate” cephalochordates to arthropods, cnidarians, and ctenophores. We also briefly highlight ongoing investigations and potential lines of inquiry that aim to understand the evolutionary relationships between these modes of specification.